2023
DOI: 10.1186/s12884-022-05272-z
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making process about prenatal genetic screening: how deeply do moms-to-be want to know from Non-Invasive Prenatal Testing?

Abstract: Background Prenatal information may be obtained through invasive diagnostic procedures and non-invasive screening procedures. Several psychological factors are involved in the decision to undergo a non-invasive prenatal testing (NIPT) but little is known about the decision-making strategies involved in choosing a specific level of in-depth NIPT, considering the increased availability and complexity of NIPT options. The main aim of this work is to assess the impact of psychological factors (anxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…While the uptake of NIPT did increase slightly after its introduction, most women still declined prenatal testing 27 . The data gathered from this study as well as from studies in other countries clearly indicate that appropriate counseling is the key to achieving high levels of informed test‐choice decisions rather than the test itself 27–33 …”
Section: The Case In Favormentioning
confidence: 74%
See 1 more Smart Citation
“…While the uptake of NIPT did increase slightly after its introduction, most women still declined prenatal testing 27 . The data gathered from this study as well as from studies in other countries clearly indicate that appropriate counseling is the key to achieving high levels of informed test‐choice decisions rather than the test itself 27–33 …”
Section: The Case In Favormentioning
confidence: 74%
“…27 The data gathered from this study as well as from studies in other countries clearly indicate that appropriate counseling is the key to achieving high levels of informed test-choice decisions rather than the test itself. [27][28][29][30][31][32][33] Another initial fear was that the introduction of NIPT would result in a drastic decrease in the livebirth prevalence of Down syndrome. A register study of the period 2014-2018, which included the start of NIPT as a first-tier test in 2017, concluded this was not the case.…”
Section: Societal and Ethical Aspectsmentioning
confidence: 99%
“…Patients cannot be properly counseled on screening tests such as NIPT without discussing diagnostic tests such as CVS or amniocentesis. Furthermore, the nuances of prenatal genetic test results should be explained to patients prior to performing the test, as some patients may be familiar with the results from NIPT (including the risk of trisomy 21, 18, or 13), but they may be less familiar with the diagnostic testing capabilities available to them, such as comprehensive chromosomal aneuploidy assessment [ 25 ]. Patients should also comprehend the potential for uncertain results or incidental findings prior to the testing rather than afterward [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these women are also characterized by active search for information in order to examine all the possible future impacts of their choice. Furthermore, a study on the psychological variables that affect the decision to perform a specific type of NIPT 36 found that women with higher levels of concern and anxiety for the fetus showed preferences for more expanded screening panel in terms of the number of conditions that are tested. These results are consistent with the finding in our HCs cohort: a search for precise, not‐probabilistic information is a way to manage uncertainty, and is characteristic of people with high intolerance to uncertainty and a high cognitive need to find a solution to ambiguous situations.…”
Section: Discussionmentioning
confidence: 99%